BOLD fMRI signal characteristics of S1- and S2-SSFP at 7 Tesla - Goa, Pål Erik; Koopmans, Peter J.; Poser, Benedikt A.; Barth, Markus; Norris, David G. (Frontiers in Neuroscience, 2014)
Object: To compare the BOLD fMRI signal characteristics in the cortex and on the pial surface for a non-balanced steady-state free precession sequence (nb-SSFP) at 7 T. Materials and methods: A multi-echo nb-SSFP sequence was used for high resolution fMRI at 7 T. Two S1 (S+) echoes at different echo times were acquired together with an S2 (S-) echo. The primary visual cortex (V1) was examined using a reversing checkerboard paradigm at an isotropic resolution of 0.75 mm, with 35 volumes acquired and a total scan time of 27 minutes. Results: Significant activation was observed in all subjects for all three acquired echoes. For the S1 signal at the longer TE, the activation induced signal change was about 4% in the cortex and 10 % at the cortical surface, while for S2 the corresponding values were 3% and 5%. Conclusion: For both S1 and S2 data, the BOLD signal peaks at the pial surface. The large pial surface signal change in S2 may be caused by dynamic averaging around post-capillary vessels embedded within CSF. This is made possible by the long diffusion times of the pathways contributing to the S2 signal and the relatively high diffusion coefficient of CSF. The results indicate that S2-SSFP might not be a suited alternative to spin-echo for high-resolution fMRI at 7 T.